A study on the relationship between factors contribute to the Social Network Sites (SNS) addiction among undergraduate students in UiTM Cawangan Kedah / Mohamad Hisham Azli …[et al.] - Azli, Mohamad Hisham; Iberahim, Muhammad Iqram (2017)
The rising trend on the utilization of Social Network Sites (SNS) has become in a such popular, drastic way to the extent that it has almost inevitable for one to actually ignore to not own at least one accounts from those sites. Such uses shall result in the excessive fashion that would inhibit unintended, unhealthy consequences. The study examines on how the SNS would affect by the personality characteristic, health concern and social environment from the standpoint of students that would be the primary respondent along the study process since they are essentially one of the later generation that shall depend on the usage of SNS in the very daily routine. A stratified sampling technique had been used by taking a sample of 148 students of undergraduate degree from UiTM Cawangan Kedah has been selected in the study. In analyzing the findings, researchers used descriptive statistics and Pearson Correlation by using Statistical Package for Social Science (SPSS). The personality, health concern and social environment factors of the students toward SNS were examined. The results indicate that there is negative relationship between personality characteristics, health concern and social environment towards SNS addiction. This study recommended that the researchers should more focusing on wider scope which are study on others campus or IPTA, use more methods and use more independent variables to improve and get better results.